2012
DOI: 10.1371/journal.pone.0042177
|View full text |Cite
|
Sign up to set email alerts
|

β-Cell Regeneration Mediated by Human Bone Marrow Mesenchymal Stem Cells

Abstract: Bone marrow mesenchymal stem cells (BMSCs) have been shown to ameliorate diabetes in animal models. The mechanism, however, remains largely unknown. An unanswered question is whether BMSCs are able to differentiate into β-cells in vivo, or whether BMSCs are able to mediate recovery and/or regeneration of endogenous β-cells. Here we examined these questions by testing the ability of hBMSCs genetically modified to transiently express vascular endothelial growth factor (VEGF) or pancreatic-duodenal homeobox 1 (PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 56 publications
(84 reference statements)
3
29
0
1
Order By: Relevance
“…Additionally; the anti-insulin immunostaining of the cells, used in this study, confirmed that the damage was mainly in the β-cells. This finding was shown in other studies after 25 days of diabetes induction [27] and after 6 weeks survival [28].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Additionally; the anti-insulin immunostaining of the cells, used in this study, confirmed that the damage was mainly in the β-cells. This finding was shown in other studies after 25 days of diabetes induction [27] and after 6 weeks survival [28].…”
Section: Discussionsupporting
confidence: 88%
“…[5] Similar results were reported by Milanesi et al [28] who studied the transplantation of human bone marrow MSCs into diabetic animal models on histological and immunohistochemical basis. They found that the human stem cells had homed in the pancreas and regenerated into β-cells with complete cure after 6 weeks from transplantation [28].…”
Section: Discussionsupporting
confidence: 76%
“…They are also a class of stem cells with the potential for directional or multi-directional differentiation, and can differentiate into bone cells, cartilage cells, or fat cells. These cells can differentiate into osteogenic tissue, adipose tissue, and many other tissues under the influence of different factors (Shi et al, 2011;Milanesi et al, 2012). We speculate that PEMFs can help promote the directional differentiation of BMSCs into osteogenic tissue and inhibit the differentiation of BMSCs into other tissues, thereby promoting the healing of fractures.…”
Section: Introductionmentioning
confidence: 74%
“…This supposition could occur through change in the tissue microenvironment which was considered the most important mechanism of action of the mesenchymal stem cells [37] . This change could explain the ability of human BMSCs to treat the autoimmune type of diabetes (type I) [38] most probably through the ability of BMSCs to stop anti β -cells specific T-cell proliferation in the pancreas. Furthermore they could protect the newly formed β -cells from being destroyed by T-cells through secretion of immunomodulatory factors [34] .…”
Section: Streptozotocin Was Reported In Previous Studiesmentioning
confidence: 99%